(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is devoted to improving the pedagogical mechanism for the education and legal protection of young athletes with a special emphasis on academic lyceums. Academic lyceums emphasize effective practices such as an integrated curriculum, time management and psychological support, with the goal of developing clear rules and standards that provide legal protection for athletes and create conditions for the balanced development and successful performance of young athletes.